Cloud technology and capsule endoscopy: A single-center users’ experience of remote online video analysis and reporting - Costigan, Conor; Walker, Caroline; O'Connell, Jim; Omallao, Emmanuel; Manoharan, Thilagaraj; Eagle, Niamh; Bailey, Yvonne; O'Hara, Fintan; Mc Namara, Deirdre (Endoscopy International Open, 2024)
Background and study aims Telemedicine has progressed significantly in recent years, with newer, more integrated information technology systems improving healthcare delivery. The development of the world’s first cloud-based capsule platform could allow safe and timely virtual analysis of videos from a network of linked hospital centers. We aimed to assess the efficacy of Medtronic’s PillCam Remote Reader System.Methods PillCam remote reader technical data were collected from the capsule endoscopy (CE) database over 8 months. User-reported performance was collect using an online survey. Outcomes included overall procedure success, video-upload/report-download rates and speeds, encryption/decryption rates, and user/reader satisfaction.Results Data from 377 studies encompassing seven different readers was collected (318 small bowel capsules, 59 colon capsules). Overall procedure success was 100% (all videos reported). Two upload delays occurred (< 24 hours). There were no encryption/decryption errors. Seven of seven respondents felt it easy to access and use vs one of seve for the old system. Six of seven respondents felt department efficiency increased. Benefits included off-site reading and multisite-conferences. Issues included offsite difficulty accessing other hospital systems.Conclusions PillCam remote reader is a reliable, secure, and effective capsule analysis platform and should be incorporated into any CE service development plan.
Keywords: Endoscopy Small Bowel; Capsule endoscopy; Training; Quality and logistical aspects; Image and data processing, documentatiton